Deconstructing a complex obsidian "source‐scape": A geoarchaeological and geochemical approach in northwestern Patagonia. Issue 1 (17th November 2018) - Barberena, Ramiro; Fernández, María V.; Rughini, Agustina A.; Borrazzo, Karen; Garvey, Raven; Lucero, Gustavo; Della Negra, Claudia; Villanueva, Guadalupe Romero; Durán, Víctor; Cortegoso, Valeria; Giesso, Martín; Klesner, Catherine; et al.
Abstract: Northwestern Patagonia is located in a tectonically active part of the southern Andes (Argentina), which has facilitated the formation of obsidian, including pyroclastic deposits that have been affected by geomorphic processes, resulting in a complex obsidian landscape. To date, the geomorphic relocation of obsidian in the landscape has not been a focus of systematic research, and this hampers our understanding of prehistoric human mobility. We present an updated assessment of the regional availability of different obsidian types based on results from our research program, which combines geoarchaeological survey and geochemical characterization to understand the properties and distribution of obsidian. This robust "source‐scape" provides the foundation for reconstructing patterns of lithic provisioning and discard. Our results suggest that interpretations of obsidian availability across the landscape should be more nuanced than is typically acknowledged. Based on our improved "source‐scape, " we discuss the patterns observed in an archaeological X‐ray fluorescence database. When compared with the geoarchaeological reconstruction of obsidian availability, the archaeological record conforms to a distance‐decay pattern. Contrary to previous interpretations, we suggest that the distribution of obsidian types is not isomorphic with human home ranges. This geoarchaeological research program provides a basis for integrating the archaeological record of different Andean regions.